Analisis Kerusakan Main Bearing pada Unit Generator Mitsubishi BMGS - Wilarso Arso; Aswin Domodite (Universitas Medan Area, 2021)
Damage to the main bearing components on the generator set unit operating in the PLTD to supply power to PLN. Based on the initial indication of engine blow-by and high vibration in the damper area of the service meter unit (SMU): 25555. The purpose of this study is to determine the root cause of the main bearing damage that changes shape and color in the diesel engine generator set. The method used in this research is a visual inspection and removing engine components. The results and discussion of the research obtained changes in the shape and color of the main bearing, starting from the main bearing material (rotating) spalling so that it rubs against the main journal. The friction that occurs causes changes in the shape of the main bearing and causes the main bearing to rotate. The keywords on the main bearing are released due to thinning so that the main bearing rotates and closes the supply of lubricating oil to the main and rod bearings. Based on the analysis, the most likely cause of adhesive wear on Main Bearing #1 is crankshaft misalignment towards the front of the engine.